NCTB Class 7 Math Chapter Four Exercise 4.3 Solution by Math Expert. Bangladesh Board Class 7 Math Solution Chapter 4.3 “Multiplication & Division of Algebraic Expressions” Exercise 4.3 Solution.

Board |
NCTB |

Class |
7 |

Subject |
Math |

Chapter |
4.3 |

Chapter Name |
“Multiplication & Division of Algebraic Expressions” |

Exercise |
4.3 Solution |

**Exercise:- 4.3**

**(1) Solution:-** 3a^{2} b x (-4ab^{2})

= – 12 a^{3} b^{3} (d)

**(2) Solution:-** 20 a^{6}b^{3}/4a^{3} b

= 5 a^{3} b^{3}(c)

**(3) Solution:-** – 25x^{3} y/ 5xy^{3}

= -5x^{2}/y^{2}

**(4) Solution:-** (8a-2b) + (7a+4b)

= (8×3-2×2) + (-7×3+4×2)

= (24-4) + (-21+8)

= 20-13

= 7.

**(5) Solution:-** x^{3}+2x^{2}-1

= (-1)^{3} +{2x (-1)^{2}}

= -1+2-1

= 0

**(6) Solution:-** 10x^{6} y^{5} z^{4}/-5×2 y^{2} z^{2}

= -2x^{4} y^{3} z^{2}

**(7) Solution:-** (a) (i) & (ii) are correct.

**(8) Solution:-** ( m^{x})^{y}

= (m^{3})^{2}

= m^{6 }Answer (d)

**(9) Solution:-** a^{0}= 1 (c)

**(10) Solution:-** x^{7}/x-^{2}

= x^{9} (a)

**(11) Solution:-** x- {x- (x-y)}

= x- (x-x +y)

= x-y (c)

**(12) Solution:-** (x +y) x [x-{x-9x-y)}]

= (x +y) x (x-y)

= x^{2}– y^{2} (d)

**(13) Solution:-** a^{5} x (-a^{3})^{0} x a-^{5}

= -a^{5+3-5}

= -a^{3} (d)

**(14) Solution:-** [2-{(1+1)-2}]

= 2-{2-2}

= 2

**(15) Solution:-** 7+2[-8-{-3-(-2-3)}-4]

= 7+2[-8-{-3+5}-4]

= 7+2[-8-2-4]

= 7+2[-14]

= 7-28

= -21

**(16) Solution:-** -5-[-8-{-4-(-2-3)}+13

= -5-[-8-{-4+5}+13

= -5-[-8-1+13]

=-5-4

= -9

**(17) Solution:-** 7-2 [-6+3(-5+2(4-3)}]

= 7-2 [-6+3{-5+2×1}]

= 7-2[-6+3x-3]

= 7-2 [-6-9]

= 7-2 (-15)

= 7+30

= 37

**(18) Solution:-** x-{a+ (y-b)}

= x-(a +y-b)

= x-a-y +b

**(19) Solution:-** 3x+(4y-z) – {a-b- (2c-4a) -5a}

= 3x+4y-z[a-b-2c+4a-5a}

= 3x+4y-z-[-b-2c]

= 3x+4y-z+b+2c

**(20) solution:-** -a-[-3b-{-2a-(-a-4b)}]

= -a-[-3b-{-2a+a+4b}]

= -a-[-3b-{-2a+a+4b}]

= -a-{-3b+a-4b}

= -a-{-7b+a}

= 7b-2a

**(22) Solution:-** {2a-(3b-5c)}-[a-{2b-(c-4a)}-7c]

= {2a-3b+5c}- [a-[2b-c+4a}-7c]

= 2a-3b+5c- [a-2b+c-4a-7c]

= 2a-3b+5c-[-3a-2b-6c]

= 2a-3b+5c+3a+2b+6c

= 5a-b+11c

**(23) Solution:-** -a+[-6b-{-15c+(-3a-9b-13c)}]

= -a+[-6b-{-15c-3a-9b-13c}]

= -a+[-6b-{-28c-3a-9b}]

= -a+[6b+28c+3a+3b]

= -a+3b+28c+3a

= 2a+3b+28c

**(24) Solution:-** -2x-[-4y-{-6z-(8x-10y+12z)}]

= -2x-[-4y-{-6z-8x+10y-12z}]

= -2x-[-4y-{-18z-8z-8z-8x+10y}]

= -2x-[-4y+18z+8x-10y]

= -2x-[-14+18z+8x]

= -2x+14y+18z+8x

= -10x+14y-10z

**(27) Solution:-** 20 –[{( 6a+3b) – (5a-2b)}+6]

= 20-[{(6a+3b-5a+2b}+6]

= 20-[{a+5b}+6]

= 20-[a+5b+6]

= 20-a-5b-6

= 14-a-5b

**(29) Solution:- ** 15a+2[3b+3(2a+2(2a+b)}]

= 15a+2[3b+3 (2a+4 a-2b)}]

= 15a + 2[3b+3 (2a-4 a-2b)}]

= 15a+2[3b-6a-6b]

= 15a+2[-3b-6a]

= 15a-6b-12a

= 3a-6b

**(29) Solution:-** [8b-3{2a-3(2b+5)-5(b-3)}]-3b

= [8b-3{2a-6b-15-5b+15}]-3b

= [8b-3{2a-11b}]-3b

= [8b-6a+33b]-3b

= 41b-6a3b

= 38b-6a

**(30) Solution:-** a-b +c-d

= a- (b-c+ d)

**(31) Solution:-** a-b-c +d-m +n-x +y

= a-(b +c-d)-m+ (n-x) +y

**(32) Solution:-** 7x-5y+8z-9

1^{st}, 7x-5y- (-8z+9)

2^{nd}, 7x+{-5y-(-8z+9)}

Therefore, 7x+{-5y-(-8z+9)}

**(33) Solution:- (a) **(15x^{2}+7x-2)- (5x-1)

= 15x^{2}+7x-2-5x+1

= 15x^{2}+2x-1

**(b)** (15x^{2}+7x-2) x (5x-1)

= 75x^{3}+35x^{2}-10x-15x^{2}-7x+2

= 75x^{3}+20x^{2}-17x+2

**(34) Solution:-** (a) A+B

= (x^{2}-xy+y^{2}) + (x^{2}+xy+y^{2})

= (x^{2}-xy+y^{2}+x^{2}+xy+y^{2})

= (2x^{2}+2y^{2})

= 2 (x^{2}+y^{2})

**(b) Solution:- **A x B

= (x^{2}-xy+y^{2}) x (x^{2}+xy+y^{2})

= x^{4}-x^{3} y+x^{2} y^{2}+x^{3}y-x^{2} y^{2}+xy^{3}+ x^{2} y^{2}– xy^{3}+y^{4}

= (x^{4}+ x^{2} y^{2}+y^{4})